Mutations of the RTEL1 Helicase in a Hoyeraal‐Hreidarsson Syndrome Patient Highlight the Importance of the ARCH Domain. Issue 5 (23rd February 2016) - Jullien, Laurent; Kannengiesser, Caroline; Kermasson, Laetitia; Cormier‐Daire, Valérie; Leblanc, Thierry; Soulier, Jean; Londono‐Vallejo, Arturo; de Villartay, Jean‐Pierre; Callebaut, Isabelle; Revy, Patrick
Abstract : Ribbon representation of a model of the 3D structure of the RTEL1 catalytic domain, highlighting the position of the ARCH domain. This model was constructed on the basis of the alignment of the RTEL1 sequences with the 3D structures of archaeal XPD. ABSTRACT: The DNA helicase RTEL1 participates in telomere maintenance and genome stability. Biallelic mutations in the RTEL1 gene account for the severe telomere biology disorder characteristic of the Hoyeraal‐Hreidarsson syndrome (HH). Here, we report a HH patient (P4) carrying two novel compound heterozygous mutations in RTEL1 : a premature stop codon (c.949A>T, p.Lys317*) and an intronic deletion leading to an exon skipping and an in‐frame deletion of 25 amino‐acids (p.Ile398_Lys422). P4's cells exhibit short and dysfunctional telomeres similarly to other RTEL1‐deficient patients. 3D structure predictions indicated that the p.Ile398_Lys422 deletion affects a part of the helicase ARCH domain, which lines the pore formed with the core HD and the iron–sulfur cluster domains and is highly specific of sequences from the eukaryotic XPD family members.